2018
DOI: 10.14814/phy2.13693
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic-induction of arginase II requires EGF-mediated EGFR activation in human pulmonary microvascular endothelial cells

Abstract: We have previously shown that hypoxia‐induced proliferation of human pulmonary microvascular endothelial cells (hPMVEC) depends on arginase II, and that epidermal growth factor receptor (EGFR) is necessary for hypoxic‐induction of arginase II. However, it remains unclear how hypoxia activates EGFR‐mediated signaling in hPMVEC. We hypothesized that hypoxia results in epidermal growth factor (EGF) production and that EGF binds to EGFR to activate the signaling cascade leading to arginase II induction and prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…In the present study, we provide further evidence that hypoxia results in release of EGF by showing that treatment of endothelial cells with an EGF neutralizing antibody during the generation of HCM prevented the subsequent HCM-induced increases in Arg2 protein and viable cell numbers in hPASMC (Figure 2). This is also consistent with our previous report in hPMVEC that culture in hypoxia-induced a robust induction of EGF mRNA, and that an EGF neutralizing antibody or siRNA transfection against EGF prevented the hypoxia-induced endothelial cell Arg2 protein expression and increase in viable endothelial cell numbers (Pool et al, 2018). It has been shown that hPASMC respond to EGF treatment with a robust proliferative response (Schultz et al, 2006;Tu et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study, we provide further evidence that hypoxia results in release of EGF by showing that treatment of endothelial cells with an EGF neutralizing antibody during the generation of HCM prevented the subsequent HCM-induced increases in Arg2 protein and viable cell numbers in hPASMC (Figure 2). This is also consistent with our previous report in hPMVEC that culture in hypoxia-induced a robust induction of EGF mRNA, and that an EGF neutralizing antibody or siRNA transfection against EGF prevented the hypoxia-induced endothelial cell Arg2 protein expression and increase in viable endothelial cell numbers (Pool et al, 2018). It has been shown that hPASMC respond to EGF treatment with a robust proliferative response (Schultz et al, 2006;Tu et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…Human PMVEC were cultured as previously described (Pool et al, 2018 ; Toby et al, 2010 ; White et al, 2017 ). Briefly, fetal hPMVEC were purchased from ScienCell (Carlsbad, CA) and were all from females including lot#5016, lot#15900, lot#17807, and lot#15902.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations